A brief review on novel pyrene based fluorometric and colorimetric chemosensors for the detection of Cu2+. (29th January 2021) - Kowser, Zannatul; Rayhan, Ummey; Akther, Thamina; Redshaw, Carl; Yamato, Takehiko
Abstract : This review article provides a detailed overview of pyrene containing colorimetric and fluorometric chemosensors based on different binding mechanisms which fulfill the criteria of affinity, selectivity and sensitivity. Abstract : The development of colorimetric and fluorometric chemosensors that capable of detecting Cu 2+ ions by a change in colour and fluorescence intensity has been described. Herein, chemosensors having pyrene functional groups as a signaling moiety are discussed in detail as pyrene derivatives show significant photophysical properties being superior to those of other commonly used scaffolds. This review article provides a detailed overview of pyrene containing chemosensors based on fluorescence mechanisms, such as excimer/exciplex formation, photoinduced electron transfer (PET), photoinduced charge transfer (PCT), aggregation induced emission (AIE), ligand to metal charge transfer process (LMCT), chelation enhanced quenching mechanism (CHEQ), Cu 2+ -selective reactions for the selective and sensitive detection of Cu 2+ . Potential future applications are also discussed because of the fact Cu 2+ ion recognition has a great significance in the biological, environmental and medical sectors.